FORMING THE READYNESS OF FUTURE TEACHERS MATHEMATICS TO CREATIVE PEDAGOGICAL ACTIVITIES - V.V. Ivanova (Academy of Cognitive and Natural Sciences, 2007)
The principal steps of forming students' readiness to their creative pedagogical activities by means of solving creative pedagogical problems (tasks) are revealed in the article.